Elektrotehniška terminologija glede na izvorni jezik - Logar Berginc, Nataša (Jezik in slovstvo, 2001)
New terms are created using the means and principles of the Slovene and the foreign language systems. In both processes, several categories of new terms may be distinguished. an analyses of the origin of new terms in Slovene electrical engineering terminology has shown that their primary source is the foreigh language system.
Keywords: Slovene; slovenščina; terminologija; terminology; elektrotehnika